TGF-β inactivation and TGF-α overexpression cooperate in an in vivo mouse model to induce hepatocellular carcinoma that recapitulates molecular features of human liver cancer - Baek, J-Y. (2010)
Hepatocellular carcinoma results from the cumulative effects of deregulated tumor suppressor genes and oncogenes. The tumor suppressor and oncogenes commonly affected include growth factors, receptors and their downstream signaling pathway components. The overexpression of TGF-α and the inhibition of TGF-β signaling are especially common in human liver cancer. Thus, we assessed whether TGF-α overexpression and TGF-β signaling inactivation cooperate in hepatocarcinogenesis using an in vivo mouse model, MT1/TGFa;AlbCre/Tgfbr2(flx/flx) mice (“TGFa;Tgfbr2(hepko)”), which overexpresses TGF-α and lacks a TGF-β receptor in the liver. TGF-β signaling inactivation did not alter the frequency or number of cancers in mice with overexpression of TGF-α. However, the tumors in the TGFa;Tgfbr2(hepko) mice displayed increased proliferation and increased cdk2, cyclin E, and cyclin A expression as well as decreased Cdkn1a/p21 expression compared to normal liver and compared to the cancers arising in the TGF-α overexpressing mice with intact TGF-β receptors. Increased phosphorylated ERK1/2 expression was also present in the tumors from the TGFa;Tgfbr2(hepko) mice and correlated with down-regulated RKIP expression, which is a common molecular event in human hepatocellular carcinoma. Thus, TGF-β signaling inactivation appears to cooperate with TGF-α in vivo to promote the formation of liver cancer that recapitulates molecular features of human hepatocellular carcinoma.